Successful Treatment of Acute Lymphoblastic Leukemia in a Child with Trisomy 21 and Complex Congenital Heart Disease with Mechanical Prosthetic Valve - Saima Alvi; Evan Shereck; Manraj K. S. Heran; George G. S. Sandor; Shahrad Rod Rassekh (Case Reports in Pediatrics)
A 10-year-old girl with trisomy 21 and complex congenital heart disease presented with acute lymphoblastic leukemia. Her chemotherapy required modifications due to poor baseline cardiac status and a mechanical prosthetic heart valve that was dependent on anticoagulation. We describe our management including the use of low-molecular-weight heparin as anticoagulation for a mechanical heart valve, the safe delivery of intrathecal chemotherapy included bridging with unfractionated heparin, and the use of fluoroscopic guidance to minimize the risk of bleeding. Adjustments were made to avoid anthracyclines. The child tolerated therapy well without complications and remains relapse free five years after diagnosis.